COMBINATION OF EFFLEURAGE AND KNEADING MASSAGE CAN REDUCE INTENSITY OF DYSMENORRHEA - Putri Lisdiana Rahmawati; Sri Ratna Dwiningsih; Lilik Herawati (Indonesian Midwifery and Health Sciences Journal, 2020)
ABSTRACTBackground : Dysmenorrhea or menstrual pain has an impact in various aspects of life. There are many methods for treating dysmenorrhea like pharmacological and nonpharmacological therapy. Massage is one of the non-pharmacological therapies used to treat dysmenorrhoea. This study aims to determine the effect of a combination of effluence and kneading massage on decreasing the intensity of dysmenorrhoea pain in adolescents. Method: This research method is experimental with a pretest - posttest control group design research design. The sampling technique is simple random sampling. A total of 20 respondents were divided into 4 groups, namely the control group, the effleurage massage group, the kneading massage group, and the combination of effleurage and kneading massage groups. The instrument used was the observation sheet of the pain level Numerical Rating Scale (NRS). Results: The test results showed that there were differences in the intensity of dysmenorrhoea pain before and after intervention of effleurage, kneading, and combination of effleurage and kneading massage. The test results also showed a difference in decrease in the intensity of dysmenorrhea for all groups with a value of p = 0.009. The combination of effleurage and kneading massage is the best treatment to decrease the intensity of dysmenorrhea. Conclusion: there are differences in the effect of giving a combination of effleurage and kneading massage to the intensity of dysmenorrhoea, and the combination of effleurage and kneading massage is the best treatment to reduce the intensity of dysmenorrhoea.